Barriers to Blood Donation Among Mbarara University of Science and Technology Students. - Karugaba, Henry; Nantongo, Hanifah (Student's Journal of Health Research Africa, 2021)
Background: Blood donation is the voluntary withdrawal of blood from an individual, after undergoing some medical screening in order to ensure the safety of both the donor and the recipient. Blood donation is crucial and indispensable in the medical process of saving lives. Globally, 112.5 million blood donations were made in 180 countries in 2013. Uganda needs at least 340,000 units of safe blood annually, but usually, only 200,000 units are collected yearly. Although massive blood donation campaigns are carried out to obtain blood, there is still more demand for blood within hospitals. Student populations are considered healthy, active, and receptive, thus, regarded as potential blood donors. This study sought to explore the barriers to blood donation among MUST students. Methodology: A qualitative descriptive design was used in this study. A purposive sampling method was used to select respondents from different faculties at MUST. Four FGDs were employed in the study and data were collected using a focus group discussion guide. Inductive content analysis was used to analyze data. Results: The study revealed different barriers to blood donation among students. Three broad themes were generated from the analysis; personal barriers related to blood donation, socio-cultural variations affecting blood donation, and the barriers concerning the blood donation process. Conclusion and recommendations: Although participants reported willingness to donate blood, it was found to be affected by barriers ranging from individuals related to the system/process in which blood is collected. Addressing these barriers may improve blood donation by MUST students.